Human Very Small Embryonic-Like Stem Cells Are Present in Normal Peripheral Blood of Young, Middle-Aged, and Aged Subjects - Hanna Sovalat; Maurice Scrofani; Antoinette Eidenschenk; Philippe Hénon (Stem Cells International)
The purpose of our study was to determine whether the number of human very small embryonic-like stem cells (huVSELs) would vary depending on the age of humans. HuVSELs frequency was evaluated into the steady-state (SS) peripheral blood (PB) of healthy volunteers using flow cytometry analysis. Their numbers were compared with volunteers’ age. Blood samples were withdrawn from 28 volunteers (age ranging from 20 to 70 years), who were distributed among three groups of age: “young” (mean age, 27.8 years), “middle” (mean age, 49 years), and “older” (mean age, 64.2 years). Comparing the three groups, we did not observe any statistically significant difference in huVSELs numbers between them. The difference in mRNA expression for PSC markers as SSEA-4, Oct-4, Nanog, and Sox2 between the three groups of age was not statistically significant. A similar frequency of huVSELs into the SS-PB of young, middle-aged, and aged subjects may indicate that the VSELs pool persists all along the life as a reserve for tissue repair in case of minor injury and that there is a continuous efflux of these cells from the BM into the PB.